Shakespeare, law, and marriage - Sokol, B. J. (Cambridge University Press, 2003)
This interdisciplinary study combines legal, historical and literary approaches to the practice and theory of marriage in Shakespeare's time, and discovers a wide range of examples in a selection of Shakespeare's plays.